The effects of lutein/ zeaxanthin (Lute-gen®) on eye health, eye strain, sleep quality, and attention in high electronic screen users: a randomized, double-blind, placebo-controlled study - Lopresti, A. L.; Smith, S. J. (Frontiers in Nutrition, 2025)
BackgroundLutein and zeaxanthin are fat-soluble antioxidant nutrients that have evidence of beneficial effects on vision and eye health.PurposeExamine the effects of supplementation with lutein and zeaxanthin isomers (Lute-gen®) on eye health, eye strain, sleep quality, and attention in high electronic screen users.Study designTwo-arm, 6-month, parallel-group, randomized, double-blind, placebo-controlled trial.MethodsSeventy volunteers aged 18 to 65 who used electronic screens for more than 6 h daily were supplemented with 10 mg of lutein and 2 mg of zeaxanthin-isomers or a placebo. Outcome measures included several ophthalmic examinations comprising the Schirmer tear test, photo-stress recovery time, contrast sensitivity, tear film break-up time, and self-report measures of visual fatigue, computer vision, sleep quality and attention.ResultsCompared to the placebo, lutein and zeaxanthin supplementation was associated with greater improvements in the Schirmer tear test, photo-stress recovery time, and tear film break-up time. However, there were no between-group differences in the change in self-report measures or contrast sensitivity. Lutein and zeaxanthin supplementation was well-tolerated, with no reports of serious adverse reactions or clinically significant changes in safety blood measures, including liver function, renal function, blood lipids, and full blood examination.ConclusionThe results from this study provide support for the beneficial effects of 6 months of lutein and zeaxanthin supplementation on regular users of electronic screens. Compared to the placebo, there were improvements in several ophthalmic examinations for dry eyes and visual health. However, these findings were not corroborated by group differences in the administered self-report measures. Lutein and zeaxanthin were well tolerated, with no serious adverse effects or significant changes in vital signs or blood safety measures.